2022
DOI: 10.3390/su142114330
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Integration and Its Impact on Operating Performance: Evidence from Chinese Online Companies

Abstract: The present study explores the effect of supply chain integration on the operational performance of an internet-based online business based in China. The study is based on primary data collected through a questionnaire distributed to supply chain professionals of the stated companies. After distributing the questionnaire and collecting the responses, an exploratory factor analysis is conducted to validate the instrument. Afterward, the confirmatory factor analysis (CFA) analysis is conducted, and finally, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 70 publications
4
10
0
1
Order By: Relevance
“…The most recent empirical study also presented significant evidence of organizational performance on supply chain performance for Chinese internet businesses in terms of operational, environmental, and economic performance (Zeng et al, 2022). Additionally, there is a clear connection between operational success and supply chain networks, which over time increases the business's efficiency (Govindan et al, 2020;Zhang et al, 2022) Thus, it can be concluded that a firm's performance aligns the supply chain for better performance under normal conditions, but in the COVID-19 pandemic scenario, the online businesses have performed better than the physical businesses due to the abrupt shutdowns and significant fall in demand for their products, which have caused severe business risk (Pantano E. et al, 2020;Udofia et al, 2020). Hence, it is believed that the firm's performance adds to the supply chain performance.…”
Section: Impact Of Firm Operational Performance On Supply Chain Perfo...mentioning
confidence: 99%
“…The most recent empirical study also presented significant evidence of organizational performance on supply chain performance for Chinese internet businesses in terms of operational, environmental, and economic performance (Zeng et al, 2022). Additionally, there is a clear connection between operational success and supply chain networks, which over time increases the business's efficiency (Govindan et al, 2020;Zhang et al, 2022) Thus, it can be concluded that a firm's performance aligns the supply chain for better performance under normal conditions, but in the COVID-19 pandemic scenario, the online businesses have performed better than the physical businesses due to the abrupt shutdowns and significant fall in demand for their products, which have caused severe business risk (Pantano E. et al, 2020;Udofia et al, 2020). Hence, it is believed that the firm's performance adds to the supply chain performance.…”
Section: Impact Of Firm Operational Performance On Supply Chain Perfo...mentioning
confidence: 99%
“…Structural equation modelling was used in this study to investigate the interrelationships between two categories of variables, latent and observable variables, while taking measurement errors into account. SEM is an excellent tool for assessing the causal link between endogenous variables (also known as the structural model in SEM) and as such considered appropriate for this study to understand the relationship between latent and observed variable of this study [ 56 , 57 ]. The “Partial least squares structural equation modelling” (PLS-SEM) was utilised to analyze the survey data and test the hypothesized relationships in the conceptual model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…SmartPLS4 software was utilised to test the study's hypothesis the causal relationship among the assessed items. This followed the approach of [ 74 , 57 ]. The SEM analysis presented in Fig.…”
Section: Hypothesis Testingmentioning
confidence: 99%
“…Utilizing digital technology and systems to promote smooth communication, cooperation, and coordination across different stakeholders throughout the supply chain system is known as "digitalizing supply chain" [18]. It includes integrating data, technologies, and processes to increase operational effectiveness, real-time visibility, and decision-making.…”
Section: Literature Review 21 Digitalization Of Supply Chainmentioning
confidence: 99%